PENGARUH SANKSI ADMINISTRASI DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR - Mahdani, Tia Mulya; Ismatullah, Ismet (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The purpose of this study was to determine the effect of administrative sanctions and service quality on taxpayer compliance in paying motorized vehicle taxes at SAMSAT Sukabumi City Region. The research method uses quantitative with an associative approach. The population in this study were motor vehicle taxpayers registered at SAMSAT Sukabumi City. The sample in this study were 100 people. The sampling technique used was purposive sampling. Data analysis using WarpPLS 7.0 application. The results showed that R² was 0.48, it could be concluded that administrative sanctions and service quality had a simultaneous effect on taxpayer compliance in paying motorized vehicle taxes by 48%.